Risk impact of SARS-CoV-2 coronavirus and spike protein on cardiac tissue: a comprehensive review - Šerý, O; Dziedzinska, R (Physiological research, 2024)
The global COVID-19 pandemic, caused by SARS-CoV-2, has led to significant morbidity and mortality, with a profound impact on cardiovascular health. This review investigates the mechanisms of SARS-CoV-2's interaction with cardiac tissue, particularly emphasizing the role of the Spike protein and ACE2 receptor in facilitating viral entry and subsequent cardiac complications. We dissect the structural features of the virus, its interactions with host cell receptors, and the resulting pathophysiological changes in the heart. Highlighting SARS-CoV-2's broad organ tropism, especially its effects on cardiomyocytes via ACE2 and TMPRSS2, the review addresses how these interactions exacerbate cardiovascular issues in patients with pre-existing conditions such as diabetes and hypertension. Additionally, we assess both direct and indirect mechanisms of virus-induced cardiac damage, including myocarditis, arrhythmias, and long-term complications such as 'long COVID'. This review underscores the complexity of SARS-CoV-2's impact on the heart, emphasizing the need for ongoing research to fully understand its long-term effects on cardiovascular health. Key words: COVID-19, Heart, ACE2, Spike protein, Cardiomyocytes, Myocarditis, Long COVID.
Keywords: Virus Internalization; Spike Glycoprotein, Coronavirus; Animals; Humans; Angiotensin-Converting Enzyme 2; lidé; Myocytes, Cardiac; zvířata; SARS-CoV-2; angiotensin-konvertující enzym 2; internalizace viru; glykoprotein S, koronavirus; Heart Diseases; COVID-19; kardiomyocyty; nemoci srdce